Pengaruh pendidikan kesehatan tentang dismenore terhadap tingkat pengetahuan remaja putri - Pebiyana Dwiyanti; Iwan Ardian; Nutrisia Nu’im Haiya (JOURNAL OF Community Health Issues, 2026)
Background: Dysmenorrhea is a common reproductive health problem among adolescent girls and can interfere with learning activities as well as quality of life. Limited knowledge regarding dysmenorrhea often leads to inappropriate management and inadequate preventive efforts. Health education is considered an effective strategy to improve adolescents’ understanding of dysmenorrhea and promote appropriate coping behaviors. Purpose: To examine the effect of health education about dysmenorrhea on the level of knowledge among female adolescents. Methods: This study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest method. The population consisted of female students at Sultan Agung 3 Islamic Senior High School, Semarang. A total of 82 respondents were selected using purposive sampling. Health education was delivered through an educational lecture using PowerPoint media in a single session. Data were collected using a knowledge questionnaire on dysmenorrhea and analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Results: A significant increase in the level of knowledge after the provision of health education. Statistical analysis indicated a significant difference between pretest and posttest scores with a p-value of 0.001 (p < 0.05). Conclusion: Health education about dysmenorrhea has a significant effect on improving the knowledge of female adolescents.   Keywords: Adolescent girls; Dysmenorrhea; Health education; Knowledge level.   Pendahuluan: Dismenore merupakan salah satu masalah kesehatan reproduksi yang sering dialami oleh remaja putri dan dapat mengganggu aktivitas belajar serta kualitas hidup. Rendahnya tingkat pengetahuan tentang dismenore berpotensi menyebabkan penanganan yang kurang tepat dan minimnya upaya pencegahan. Pendidikan kesehatan menjadi salah satu intervensi yang dapat meningkatkan pemahaman remaja putri mengenai dismenore. Tujuan: Untuk menganalisis pengaruh pendidikan kesehatan tentang dismenore terhadap tingkat pengetahuan remaja putri. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen melalui rancangan one group pretest–posttest. Sampel penelitian berjumlah 82 siswi yang dipilih menggunakan teknik purposive sampling. Pendidikan kesehatan diberikan melalui metode ceramah edukatif menggunakan media PowerPoint dalam satu kali pertemuan. Pengumpulan data dilakukan menggunakan kuesioner tingkat pengetahuan tentang dismenore, kemudian dianalisis dengan uji Wilcoxon Signed Rank Test pada taraf signifikansi α = 0.05. Hasil: Adanya peningkatan tingkat pengetahuan remaja putri setelah diberikan pendidikan kesehatan. Uji statistik menunjukkan perbedaan yang bermakna antara nilai pretest dan posttest dengan nilai p = 0.001 (p < 0.05). Simpulan: Pendidikan kesehatan tentang dismenore berpengaruh signifikan terhadap peningkatan tingkat pengetahuan remaja putri.   Kata Kunci: Dismenore; Pendidikan Kesehatan; Remaja Putri; Tingkat Pengetahuan.